Model of Prevention of Social Conflict which Multi Dimensions Based on Local Wisdom of Community Adat Dalihan Na Tolu - Harahap, Anwar Sadat; Hasibuan, Ahmad Laut (Brawijaya Law Journal, 2018)
The main purpose of this research is to find a model of punishment in preventing social conflict on local wisdom of Dalihan na Tolu indigenous people. The questions posed in this research include the multi-dimension social conflict prevention model based on local wisdom of Indonesia, the deliberation stage of preventing such conflict and strategies adopted by local wisdom to resolve social conflict. The research further focuses its examination on local society that is Dalihan na Tolu indigenous people. This research uses empirical juridical research method, which is departed from local wisdom norms, or known as adat laws and examines the application of such laws in society. This research proposes that the multi-dimensional model of social conflict prevention should be carried out using the rules contained in: Dalihan na Tolu custom, Sipaingot, Pastak ni Paradaton, Uhum dohot Patik, Hapantunon, Tutur dohot Poda, Marga, Martahi, Mangupa. While the system and strategies of negotiation to reach consencus in preventing multi-dimensional social conflict based on the following norms: Tahi Ungut-ungut, Tahi Dalihan na Tolu, Tahi Godang Parsahutaon and Tahi Godang Haruaya Mardomu Bulung. It is argued that the punishment model usually used by Batak community should be adopted both in preventing as well as resolving social conflict exists in society.